Bone marrow evaluation in patients with fever of unknown origin - Jha, A; Adhikari, RC; Sarda, R (Journal of Pathology of Nepal, 2012)
Bone marrow examination is commonly requested investigations in cases of fever of unknown origin, irrespective of alteration in hematological parameters. More than 200 etiologies are associated with fever of unknown origin, and they are broadly divided into infectious, neoplastic, collagen vascular diseases, miscellaneous and undiagnosed. Many of these conditions directly or indirectly affect bone marrow. Marrow may show changes in cellular components, interstitium or in the blood vessels depending on the underlying local or systemic conditions. The three main hematopoietic cell lines may show variable hyperplasia, hypoplasia or aplasia of one or more than one cell lines, and occasionally dyspoiesis. Interstitium may show fibrosis, gelatinous transformation, or infiltration by abnormal cells. Amyloid deposits may be seen around blood vessels. Marrow may also show granulomas, infectious agents or neoplastic cells. Various reactive changes can be seen in the bone marrow in neoplastic, infectious and in connective tissue diseases. Infectious agents can be cultured from the marrow aspirate or can be demonstrated in marrow. DOI: http://dx.doi.org/10.3126/jpn.v2i3.6029 JPN 2012; 2(3): 231-240